Maintaining Minority Languages in Transnational Contexts - Bianco, Joseph Lo; Pauwels, Anne; Winter, Joanne (Palgrave studies in minority languages and communities., 2007)
Deals with challenges to the maintenance of minority (or community) languages in this era of globalization and increasing transnational movements of people. The contributors, experts in language policy, language maintenance and multilingualism offer complementary perspectives from Australia and Europe on the maintenance of linguistic diversity.